Working Behind Bars: Employed Prisoners’ Perception of Professional Training and Employment in Prison - Laskov, Ronit Peled; Timor, Uri (International Journal of Criminology and Sociology, 2018)
The research is aimed at examining the perceptions and attitudes of prisoners employed in enterprises in prison vis-à-vis employment and deriving conclusions regarding the impact of employment on the lives of prisoners in prison and its contribution to advancing their rehabilitation. Doing time is generally a painful experience, both physically and mentally, and often adversely influences prisoners’ life after release. Programs and activities have been developed in prisons in many countries, including Israel, to mitigate these impacts and at the same time reduce recidivism following release. A key such program is employment in enterprises within the prison walls, including training of prisoners in a variety of professions. In the framework of the present qualitative research 20 prisoners employed in enterprises in Israeli prisons were interviewed, and these aired their perceptions regarding employment and its effects. Three main themes and 18 sub-themes defining the attitudes of the prisoners to the issue emerged from the interviews. The first two themes are: employment provides benefits and alleviates the pains of imprisonment; and employment helps prisoners’ rehabilitation. The third theme emerging from the statements of an isolated number of prisoners is: employment is an act of exploitation on the part of the Prison Service and serves no useful purpose. The overall conclusion of the study is that employment in enterprises in prison is generally perceived by the prisoners as positive and contributory, in terms of both reducing the damage caused by imprisonment and raising the likelihood of the prisoner being rehabilitated through employment following his release.